2008
DOI: 10.1086/593104
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Infection and Response to Antiretroviral Therapy (ART) in a South African ART Program

Abstract: Background Coinfection with hepatitis B virus (HBV) and human immunodeficiency virus (HIV) is common in Africa; however, the impact of HBV infection on the outcomes of antiretroviral therapy programs is unclear. We evaluated the impact of chronic hepatitis B on HIV virologic response, changes in CD4 cell count, hepatotoxicity, and mortality among Africans receiving highly active antiretroviral therapy (HAART). Methods We conducted a retrospective cohort study involving a workplace HAART program in South Afri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
104
5
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(127 citation statements)
references
References 26 publications
(30 reference statements)
17
104
5
1
Order By: Relevance
“…[19] Although hepatotoxicity of HAART is increased by the presence of HBV, studies have shown that patients with high HBV-DNA baseline levels have a higher risk of hepatotoxicity than non-HBV-infected HIV patients. [9] Most of the patients in the current study had undetectable and low viral loads prior to therapy initiation and within a year on HAART, which may explain why the average level of aminotransferase was not significantly higher in these patients, concurring with the observation of Boyles and Cohen [8] that aminotransferase may be an insensitive marker for HBV infection. It could be assumed that most of the patients on HAART in the studied population had a lower risk of developing hepatotoxicity within the first year of treatment.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…[19] Although hepatotoxicity of HAART is increased by the presence of HBV, studies have shown that patients with high HBV-DNA baseline levels have a higher risk of hepatotoxicity than non-HBV-infected HIV patients. [9] Most of the patients in the current study had undetectable and low viral loads prior to therapy initiation and within a year on HAART, which may explain why the average level of aminotransferase was not significantly higher in these patients, concurring with the observation of Boyles and Cohen [8] that aminotransferase may be an insensitive marker for HBV infection. It could be assumed that most of the patients on HAART in the studied population had a lower risk of developing hepatotoxicity within the first year of treatment.…”
Section: Discussionsupporting
confidence: 88%
“…[8,11,13] However, high prevalence rates have also been documented; for example, Hoffmann et al reported a prevalence of 20% among male mine workers in several regions of South Africa. [9] In Gauteng Province, exposure to HBV, based on HBsAg and antiHBc, of 39% was documented in HIV-infected women. [10] The current study also examined the effect of declining CD4+ cell count on the prevalence of HBV, as reactivation is expected to be proportional to the level of immune depreciation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, HIV-infected patients co-infected with HBV have an increased risk for antiretroviral therapy-related hepatotoxicity, particularly when HBV DNA levels exceed 10,000 copies/ml 4 . Both can lead to chronic disease, cancer and death and neither can be eradicated with the use of current therapies.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the impact of HIV on HBV-replication has largely been unexplored in Nigeria. Furthermore, with the wide use of antiretroviral therapy (ART) for HIV-infected individuals, antiretroviral drug-induced hepatotoxicity has been more frequently reported in HIV/HBV coinfected subjects with high HBV replication [16]. This further makes determinations of HBV replication markers a priority in co-infected patients in a country such as Nigeria where access to ART is being scaled up.…”
Section: Introductionmentioning
confidence: 99%